Riqueza e pambiogeografia de samambaias e licófitas da província da caatinga - Silvestre, Leandro Costa (2014)
Ferns and Lycophyta species that occur in the Caatinga Province were recorded and their biogeographical relations established using a Pambiogeographic analysis. The study aimed to conduct an analysis of the Panbiogeography of ferns and lycophytes species inventoried for the Province of Caatinga, evaluating their global distribution, as well as the explanation of this distribution based on the plant geography of South America and biogeographic processes. 52 species of ferns and five of lycophytes were recorded. The most represented genera in the neotropics were Anemia Sw (10 spp.), Adiantum L (2 spp.), Doryopteris J. Sm. (2 spp.), Sticherus C. Presl (2.spp.). About the species restricted to Brazil, only Anemia dardanoi Brade was verified as endemic to the Caatinga Province. Pambiogeographic analysis allowed the recognition of 54 individual tracks and 17 generalized tracks. The analyzes also showed 10 pambiogeographics nodes delimited to Neotropical region. The ferns and Lycophyta distribution occurrent in the Caatinga Province was mainly on seasonally dry tropical forests and Neotropical savannas in the Americas, indicating a continues distribution on these areas.